Total combustion of Methane with the help of a membrane impregnated with ∞ - Fe2O3 - Picasso, Gino (2003)
A catalytic membrane of Fe,0, prepared from impregnation of a inoxidizable steel tube (dimensions: large = 8 cm, internal diameter = 6 mm, porous surface = 1,13 cm²) with saturated solution of Fe(NO3).9H₂O, descomposed at 170 °C for 6 h and then calcined at 600 °C for 6 h. The synthesized Fe,0, was obtained in α-hematite phase following the XRD analysis. The hematite membrane was characterized by mesure of N, permeation, Knudsen diffusion coeficient and porous average radius of the membrane.The synthesized membrane has been applied in the total combustion of methane. The obtained ligth-off curves have been analyzed in a fresh membrane, after 1 day, 2 and 3 days of activity in order to check the stability of the membrane. The permeation observations were correlated with the activity of the membrane. This work is an advance of the initial part of my Ph.D. proyect in the University of Zaragoza which concerns the research of inorganic membranes in the total combustion of methane and VOCs (volatil organic compounds).